2022
DOI: 10.1186/s12966-022-01309-w
|View full text |Cite
|
Sign up to set email alerts
|

Health effects and cost-effectiveness of a multilevel physical activity intervention in low-income older adults; results from the PEP4PA cluster randomized controlled trial

Abstract: Background Older adults are the least active population in the U.S. Low-income communities have fewer physical activity (PA) resources, contributing to less PA and increased chronic disease risk. This study assessed the effect of the multilevel, peer-led, Peer Empowerment Program 4 Physical Activity (PEP4PA) on moderate-to-vigorous PA (MVPA) and health outcomes, over 2 years of follow up. Methods In a cluster-randomized controlled trial, 12 senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Crist et al examined the relationship between a peer-led group PA intervention and objective PA in older US-Americans. They found a significant increase in PA in the intervention group at 12 months, and participants maintained the increase over 2 years [ 112 ]. Chia et al found a significant positive association between companionship SOSU and objective PA in Taiwanese men and women, but the association was stronger in women [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crist et al examined the relationship between a peer-led group PA intervention and objective PA in older US-Americans. They found a significant increase in PA in the intervention group at 12 months, and participants maintained the increase over 2 years [ 112 ]. Chia et al found a significant positive association between companionship SOSU and objective PA in Taiwanese men and women, but the association was stronger in women [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings also replicated a prior study, RS 2.0, by some of us, in a larger sample and longer follow-up. Other intervention studies with interpersonal BCSs plus intrapersonal BCSs have also shown increases in PA of older adults, African American adult women, and adolescents . However, more specific evidence about the unique effects of intrapersonally vs interpersonally oriented BCSs is sparse and inconclusive .…”
Section: Discussionmentioning
confidence: 99%
“…The United Nations defines older adult as individuals age sixty and above [ 1 ]. Nevertheless, because this study's ultimate goal is to inform technological interventions designed for the low-income older adult group, this review considers older adults as individuals starting from the age of fifty years and older based on two contextual propositions: (i) the gap in life expectancy between the richest one percent and poorest one percent of individuals was 14.6 years for men and 10.1 years for women in the United States between 2001 and 2014 [ 29 ], and low-income older adults may need technological interventions related to these aging and health issues earlier in the aging process than the general population of older adults; (ii) the ‘older adults’ age classification of fifty years and above is commonly observed in large longitudinal studies on aging, such as the Health and Retirement Study in the United States 2017 [ 30 ] and the English Longitudinal Study of Ageing (ELSA) 2020 [ 31 ]; and (iii) consistent with the ‘older adults’ age range adopted in existing systematic literature reviews on factors influencing technology use by older adults [ 23 , 32 , 33 ] and empirical studies concerning low-income older adults, such as healthcare access and food insecurity [ 34 ], interventions [ 35 , 36 ], and Internet use [ 37 ].…”
Section: Introductionmentioning
confidence: 89%